In-plane shear capacity of tuff masonry walls with traditional and innovative Composite Reinforced Mortars (CRM). (20th June 2019) - Del Zoppo, Marta; Di Ludovico, Marco; Balsamo, Alberto; Prota, Andrea
Highlights: In-plane capacity of URM walls strengthened with traditional or innovative systems is investigated. Reinforced plaster or Composite Reinforced Mortar are used as strengthening. Strengthening configurations, matrix composition and grid properties are analysed. Shear stress and deformability, stiffness and energy dissipation are reported. Shear capacity enhancement up to 288%. Abstract: The effectiveness of reinforced plasters and Composite Reinforced Mortars (CRM) for increasing the in-plane shear capacity of masonry walls was investigated on a series of 32 single-leaf tuff masonry panels subjected to diagonal compression tests. Six specimens were used as control and two specimens were strengthened with reinforced plaster (steel grid 100 × 100 mm and cementitious matrix) with a thickness of 40 mm. The remaining specimens were strengthened with two different fibre reinforced lime-based mortars, characterized by different cement content ratios, and coupled with three different grids (steel grid 100 × 100 mm, GFRP grid 30 × 30 mm and GFRP grid 40 × 40 mm). Both single-sided and double-sided strengthening configurations were adopted for all strengthening solutions, to investigate the reduction in strengthening effectiveness in case of single-sided applications. The results showed that strengthening in single-sided configuration increased the shear capacity from 42% to 85% with respect to the unreinforced masonry panels (URM) average shear capacity. Conversely, strengthening in double-sided configuration led to a shear capacity increase from 138% up to 288%. Based on experimental results, reducing the matrix cement content ratios in strengthened system led to a reduction in shear capacity and energy dissipation, independently from the grid properties. Furthermore, specimens strengthened with GFRP 40 × 40 grid, although characterized by a large spacing with respect to GFRP 30 × 30, achieved an increase in the shear capacity and energy dissipation greater than other strengthened specimens clearly evidencing that the grid spacing and the interlock between grid and micro-fibres embedded in the mortar are crucial aspects for the strengthening system effectiveness.